Capacitive Humidity Sensor with a Rapid Response Time on a GO-Doped P(VDF-TrFE)/LiCl Composite for Noncontact Sensing Applications - Enkhzaya Ganbold; Parshant Kumar Sharma; Eun-Seong Kim; Do-Nam Lee; Nam-Young Kim (Chemosensors, 2023)
Humidity-sensing devices are widely utilized in various fields, including the environment, industries, food processing, agriculture, and medical processes. In the past few years, the development of noncontact sensors based on moisture detection has increased rapidly due to the COVID-19 pandemic. Moisture-detection, noncontact and breath-monitoring sensors have promising applications in various fields. In this study, we proposed a rapid-response graphene oxide (GO)-doped P(VDF-TrFE)/LiCl nanocomposite-based moisture sensor fabricated on an interdigitated electrode. The synthesis of GO/P(VDF-TrFE)/LiCl resulted in a porous structure with nano-sized holes due to the effect of LiCl. Moreover, doped GO improved the conductivity of the sensing film. The created nanoporous structure improved the recovery time better than the response time, with the times being 4.8 s and 7.8 s, respectively. Not only did our sensor exhibit rapid response and recovery times, it also exhibited a high sensitivity of 1708.8 pF/%RH at 25% to 93%RH. We also presented a real-time breath-monitoring system for noncontact sensing applications based on GO-doped P(VDF-TrFE)/LiCl composites. The results revealed that GO-doped P(VDF-TrFE)/LiCl is a good candidate for fabricating real-time moisture-detection noncontact sensing devices.